SURFACE SELECTIVITY IN THE DIRECT ELECTROCHEMISTRY OF REDOX PROTEINS - CONTRASTING BEHAVIOR AT EDGE AND BASAL PLANES OF GRAPHITE - Armstrong, F; Hill, H; Oliver, B (1984)
A comparison of the direct electrochemistry of cytochrome c, ferredoxin, and rubredoxin at edge and basal planes of pyrolytic graphite shows heterogeneous electron transfer to be catalysed at the edge surface indicating the importance of specific protein-electrode interactions.